Synthesis of an MUC1 Glycopeptide Dendrimer Based on β-Cyclodextrin by Click Chemistry - Chen, Pu-Guang; Huang, Zhi-Hua; Sun, Zhan-Yi; Li, Qian-Qian; Chen, Yong-Xiang; Zhao, Yu-Fen; Li, Yan-Mei (Synlett, 2017)
Glycopeptide dendrimers are attractive candidates for biomedical applications. Here, an efficient method for preparing multivalent MUC1 glycopeptide dendrimers based on β-cyclodextrin is described. By using copper(I) bromide and thioanisole as a catalyst system, precisely defined heptavalent conjugates were efficiently obtained. Using this heptavalent glycopeptide dendrimer, we observed multivalent effects in recognition and association processes in antibody and epitope interactions, which might have biomedical applications.
Keywords: glycopeptide dendrimers; cyclodextrin; copper catalysis; thioanisole; antibody titer; click chemistry